Christianity and Politics: Historical overview and the Contemporary Challenge - R Fastiggi & W Teasdale (Journal of Dharma, 1982)
The question of the relationship between politics and Christianity can take on a number of different nuances. In one sense, it can turn on the question of how involved should the Christian community be in the world of politics. Should Christians try to exert political pressure on governmental leaders in order to insure a moral society? Is there a "Christian position" on various political issues? Is an individual not fully Christian if he or she is not involved in the political arena?These questions have come to the forefront in recent years. The issue is certainly not a new one. There has always existed a tension between the Christian community as a spiritual, a-temporal and escha- tologically oriented body and the Christain Church as an historical, temporal and socially transforming reality. The history of Christianity is a study of variety and contrasts when it comes to the question of political involvement. On the one hand, we have the image of the monk: steeped in the numinous and transcendent, absorbed in liturgi- cal timelessness and interior meditation. What has the monk to do with the world of princes and battles or congresses and treaties?